PREVENTIVE EFFORTS OF THE DRUG AND FOOD SUPERVISORY AGENCY (BPOM) ON THE CIRCULATION OF DRIED ANCHOVY THAT CONTAINS FORMALIN IN THE CITY OF DENPASAR - Anak Agung Sagung Ngurah Indradewi; Kadek Firda Sri Astiti (Awang Long Law Review, 2022)
Since the pandemic, there have been many layoffs and many employees have been laid off. Some of them turn into business actors, they often change their direction to become agents of dried anchovies, but dried anchovies because dried anchovies cannot last long so business actors use fraudulent methods such as using formalin on their dried anchovies.The research method in this research is using empirical legal research, namely scientific research that explains legal phenomena about the occurrence of gaps between norms and community behavior (the gap between das sollen and das sein). The conclusion in this study is that BPOM's efforts on the circulation of dried anchovy containing formalin in Denpasar City, namely supervision, guidance, and testing of dried anchovy are positive for formalin or not, after testing it was found a product that was positive for formalin after that coaching was carried out by the Agency POM so as not to be resold. Obstacles in preventing the circulation of dried anchovy containing formalin in Denpasar City are: legal factors, supporting facilities and facilities, cultural factors, and other factors that hinder law enforcement such as economic factors, community factors, and law enforcement factors apart from that. the factors of traders who are difficult to be given guidance on cheating traders, lack of awareness of producers about the dangers of food containing formaldehyde.